2021
DOI: 10.1101/2021.03.21.436309
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stochasticity-induced stabilization weakens in diverse communities

Abstract: Environmental stochasticity and the temporal variations of demographic rates associated with it are ubiquitous in nature. The ability of these fluctuations to stabilize a coexistence state of competing populations (sometimes known as the storage effect) is a counterintuitive feature that has aroused much interest. Here we consider the performance of environmental stochasticity as a stabilizer in diverse communities. We show that the effect of stochasticity is buffered because of the differential response of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…We derived a formula showing that the temporal correlation at which the transition occurred decreased with the community speciation rate as an inverse relationship, reflecting weaker temporal niches from the second pathway. A recent study (Pande and Shnerb 2021) also found such an inverse relationship for a different community model with TES, but using simulations that do not allow generalization of the relationship across parameter space as our formula does. Our formula indicates that TES is less likely to have a positive net effect on richness for communities with more species, such as tropical coral and tree communities.…”
Section: Discussionmentioning
confidence: 66%
“…We derived a formula showing that the temporal correlation at which the transition occurred decreased with the community speciation rate as an inverse relationship, reflecting weaker temporal niches from the second pathway. A recent study (Pande and Shnerb 2021) also found such an inverse relationship for a different community model with TES, but using simulations that do not allow generalization of the relationship across parameter space as our formula does. Our formula indicates that TES is less likely to have a positive net effect on richness for communities with more species, such as tropical coral and tree communities.…”
Section: Discussionmentioning
confidence: 66%